MicroRNA-155 is upregulated in the placentas of patients with preeclampsia and affects trophoblast apoptosis by targeting SHH/GLi1/BCL2. (March 2021) - Wang, Zhenpeng; Shan, Yanhong; Yang, Yi; Wang, Tianshu; Guo, Zhiheng
The pathogenesis of preeclampsia (PE) is complicated and multiple risk factors have been associated with its occurrence. Still, the underlying molecular mechanisms involved in PE remain elusive. Aberrant apoptosis and insufficient invasion of trophoblasts have been observed and are considered vital pathological features in PE. Herein, we found that miR-155 can specifically degrade the mRNA of the Hedgehog ligand sonic hedgehog (SHH), using dual luciferase reporter assays. Quantitative real-time PCR found that administering miR-155 mimics or inhibitors could significantly decrease or increase the expression of SHH in the trophoblasts, respectively. The transcription levels of miR-155 in the placenta were higher in patients with PE compared to the levels in healthy pregnant women, as shown by quantitative real-time PCR. Serum levels of miR-155 could predict the diagnosis of PE by receiver operating characteristic curve analysis and diagnosis evaluation tests. A significant increase in apoptosis was observed after administering miR-155 in HTR8/SVneo cells cultured ex vivo, accompanied by reduced proliferation. Mechanistically, transcriptional activity and expression of GLi1 were also inhibited under treatment of miR-155, and could be recovered after supplying additional recombinant human SHH to primary trophoblasts from patients, as determined by luciferase activity assays and western blotting. We further found that inhibiting miR-155 increased the production of SHH and improved the phenotype in primary trophoblasts from patients with PE. Our data show that miR-155 regulates apoptosis of trophoblasts in PE, which has potential value for predicting PE risk and might be deemed as a therapeutic target for treating PE.